Carrier frequency offsets estimation for distributed MIMO system based on SOMP method - Yanyan HUANG; Hua PENG (Tongxin xuebao)
By utilizing the half invariant property of high-order cyclic cumulants,the equation of signals and its high-order cyclic cumulants was rederivated first.Then simultaneous orthogonal matching pursuit (SOMP) method was used to jointly reconstruct multiple receiving signals’ high-order cyclic cumulants.At last,according to the fourfold relationship between carrier frequency offsets and cyclic frequencies of main non-zeros high-order cyclic cumulants,multiple transmitting signals’ carrier frequency offsets were obtained.Comparing with existing algorithms,the correlation between receiving signals is fully used by the proposed algorithm,the carrier frequency offset estimation performance at low signal to noise is improved and the pilots numbers are reduced.